FAVORITISME KELOMPOK: PERSPEKTIF AGAMA ISLAM - Karimulloh, Karimulloh; Putra, Johan Satria (Dialogia: Jurnal Studi Islam dan Sosial, 2019)
The issue of religious tolerance is one of the important issues in the last decade, especially among Indonesian Muslims. Basically, Islam through the concept of morals teaches compassion for humans as well as adherents of other religions. However, on the other hand, many Muslims then limit themselves to giving a positive attitude towards other religions because of fears of violating the faith. How the attitude of Islam towards other religions has been studied in the scientific study of Islam itself. However, most of the studies carried out were case studies and comparisons. While research in Islamic psychology also began to study a lot about behavior between religious groups, such as the construct of group favoritism. But not many have used the basis of a strong Islamic study as its justification. This study tries to conduct an integrative study between the study of literature from Islamic law with empirical studies of psychology. The literature study is carried out by conducting a study and comparison of various relevant references. Empirical studies were conducted by distributing questionnaires to several Islamic adolescents in Jabodetabek on a scale of group religiosity and favoritism. Furthermore, an analysis will be carried out by comparing and correlating the results of the literature and empirical studies. While the results of this study indicate that there is no group favoritism in Islam, because brotherhood for a Muslim is not only limited to fellow Muslims, but also to fellow non-Muslims or even other creatures of God.